Experiencing mortality and transcendence in the digital age - Globokar, Roman (Poligrafi, 2025)
The rapid development of digital technology is also bringing changes to the ex-perience of mortality and transcendence. New possibilities for prolonging life and the promise of immortality are prompting a reevaluation of who human beings truly are and what path of development they should take to preserve the possibil-ity of living with dignity in the future. in the first part, i critically evaluate Yuval Harari’s provocative work Homo Deus, which suggests a transition from condi-tio humana to conditio posthumana, which is marked by desires for immortality, happiness, and divinity. He believes that algorithms play a central role in digital culture and are gaining increasing trust among people. a view called dataism is gaining prominence, which posits that all of reality is merely a collection of data. in the second part, i contrast this view with Hans Jonas’s philosophy of the organ-ism, which sees the living organism as a paradigm of being. The living organism cannot be reduced to data, and therefore, the whole of reality transcends the data level. an essential part of a living being is its mortality, which Jonas understands as both a burden and a blessing: without death, there is no new life. The last section is devoted to theological reflection on the dual character of human life alongside the first three chapters of Genesis. The fundamental biblical truth is that human-ity is created in the image of God, which means that they are created transient, vulnerable, and mortal, but at the same time transcended and called to eternity. The basic thesis of this paper is that mortality is part of that human being created in God’s image and that it is within our physicality and transience that we experi-ence the longing to transcend this world and to seek eternity. faith in a personal God, within the context of reductionist dataism, frees one from being trapped in the determinism of algorithms and gives one the courage to make responsible choices for the future of humanity.
Keywords: dataism; dataizem; digital culture; digitalna kultura; Harari, Yuval; imago Dei; Jonas, Hans; mortality; transcendenca; transcendence; umrljivost